2008
DOI: 10.4238/vol7-1gmr365
|View full text |Cite
|
Sign up to set email alerts
|

Molecular variability in Brycon cf. pesu Muller and Troschel, 1845 (Characiformes: Characidae) from the Araguaia-Tocantins Basin

Abstract: AbSTRACT. Brycon pesu is a small-sized fish distributed throughout the Amazon and Orinoco Basins and other coastal basins of northeastern South America. Brycon cf. pesu specimens from the Araguaia-Tocantins Basin are currently separated into two morphotypes, Brycon sp1 and Brycon sp2, owing to different coloration of their anal fin. Brycon sp2 has a reddish margin stripe on the anal fin which morphologically distinguishes it from Brycon sp1. In the present research, nuclear and mitochondrial markers were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…The 12 nucleotide substitutions in the mtDNA control region of P. squamosissimus clearly indicated that the PI and TO native populations went through independent evolution and became genetically differentiated. The high level of intraspecific genetic similarity (96%) between the PI and TO P. squamosissimus populations resembled levels of genetic similarities among populations of other Neotropical fish species also analysed for polymorphism in the mtDNA control region (Prioli et al , 2002; Oliveira et al , 2006; Panarari‐Antunes et al , 2008). Genetic differentiation based on mtDNA control region polymorphism has been found relatively high among species, including the closely related species Cichla kelberi Kullander & Ferreira 2006 (previously Cichla monoculus Spix & Agassix 1831), Cichla piquiti Kullander & Ferreira (previously Cichla sp.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The 12 nucleotide substitutions in the mtDNA control region of P. squamosissimus clearly indicated that the PI and TO native populations went through independent evolution and became genetically differentiated. The high level of intraspecific genetic similarity (96%) between the PI and TO P. squamosissimus populations resembled levels of genetic similarities among populations of other Neotropical fish species also analysed for polymorphism in the mtDNA control region (Prioli et al , 2002; Oliveira et al , 2006; Panarari‐Antunes et al , 2008). Genetic differentiation based on mtDNA control region polymorphism has been found relatively high among species, including the closely related species Cichla kelberi Kullander & Ferreira 2006 (previously Cichla monoculus Spix & Agassix 1831), Cichla piquiti Kullander & Ferreira (previously Cichla sp.…”
Section: Discussionmentioning
confidence: 73%
“…The mitochondrial DNA (mtDNA) D‐loop control region is the fastest evolving and the most variable sequence of metazoan DNA. It has been the main molecular marker of choice for analyses of intraspecific genetic variation, including fish species (Panarari‐Antunes et al , 2008; Pie et al , 2009; Antunes et al , 2010; Hirayama et al , 2010; Lo Presti et al , 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear markers such as RAPD (Random Amplified Polymorphic DNA), and sequences of mitochondrial DNA (mtDNA) have been useful in the studies of the genetic structure of populations, phylogeographic relations and phylogenetic reconstruction in fishes (Sivasundar et al, 2001;Liu et al, 2005;Lage and Kornfield, 2006;Antunes et al, 2010). Molecular studies have been developed with several species of the genus Brycon (Wasko and Galetti, 2002;Barroso et al 2003;Wasko and Galetti, 2003;Wasko et al 2004;Santis et al, 2007;Panarari-Antunes et al, 2008;Antunes et al, 2010). However, there are few genetic studies with B. orbignyanus, and those assessing the genetic diversity of natural populations are needed, so that they can be used in programs of conservation of the species.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently used mitochondrial DNA D-loop has been the main molecular marker to analyze genetic variation, including fish species (Panarari-Antunes et al, 2008;Hirayama et al, 2010;Lo Presti et al, 2010).…”
Section: Genrementioning
confidence: 99%